Mixed tau and TDP-43 pathology in a patient with unclassifiable primary progressive aphasia. Issue 1 (2nd January 2016) - Flanagan, Eoin P.; Duffy, Joseph R.; Whitwell, Jennifer L.; Vemuri, Prashanthi; Dickson, Dennis W.; Josephs, Keith A.
Abstract : Classifying primary progressive aphasia (PPA) into variants that may predict the underlying pathology is important. However, some PPA patients cannot be classified. A 78-year-old woman had unclassifiable PPA characterized by anomia, dysarthria, and apraxia of speech without agrammatism. Magnetic resonance imaging revealed left mesial temporal atrophy and 18-flourodeoxy-glucose positron emission tomography showed left anterior temporal and posterior frontal (premotor) hypometabolism. Autopsy revealed a mixed tauopathy (argyrophilic grain disease) and transactive response-DNA-binding-protein-43 proteinopathy. Dual pathologies may explain the difficulty classifying some PPA patients and recognizing this will be important as new imaging techniques (particularly tau-positron emission tomography) are introduced and patients begin enrollment in clinical trials targeting the underlying proteinopathy.